Nilai dan profesionalisme menurut Imam Al-Juwayni: fokus terhadap isu-isu kepimpinan, aqidah dan perselisihan ummah - Mohd Fadzhil Mustafa,; Mohdmad Sabri Haron,; Hasnan Kasan, (Universiti Kebangsaan Malaysia, 2009)
Values are a timeless universal need. Islam has provided mankind with a set of values that are proven essential for everyday life. A great number of Islamic scholars have discussed these values extensively in order to assist understanding and to develop a practical guide for Muslim society. Among these scholars are Imam al-Juwayni. In this article, the authors will focus on al-Juwayni’s contributions toward providing a comprehensive framework on Islamic values applicable in the fields of leadership, religious faith as well as dealing with factional disputes between Muslim ummah